The Debates on Ecology and Religion Leading to Pope Francis' Encyclical Laudato si' on Integral Ecology - Rigal-Cellard, Bernadette (International journal for the study of new religions, 2023)
This paper focuses on the vision religions have of nature and of the Anthropocene through an analysis of the current theoretical discourse on the links between Christianity and climate change. The first step was Lynn White Jr's 1967 article, "The Historical Roots of Our Ecologic Crisis", which accused Christianity of being the prime perpetrator of the destruction of nature. Orthodox Patriarch Bartholomew opened the second stage when he delivered his Address on the Environment in 1997. The third stage is the Anthropocene theory of Paul Crutzen (2002) who accused humans of being responsible for the destruction of nature. These debates led to the publication in May 2015 of Pope Francis’ encyclical Laudato si', a radical plea for integral ecology. Its contents will be analysed to show its reaffirmation of the Church teachings on nature as divine Creation, on man as a sinner responsible for the ecological disaster, and on the poor as deserving attention and care. Finally, the Laudato si' Movement, spawned by the encyclical, will be presented as one good example of the powerful dynamogenic function of religion.